Mutant Fam20c knock-in mice recapitulate both lethal and non-lethal human Raine Syndrome - Mengnan Chen; Dongmei Sun; Siu-Pok Yee; Zhaoyang Yuan; Li Lin; Bing Cui; Yi Wang; Chao Liu; Peihong Liu (BMC Molecular and Cell Biology)
Abstract Background Inactivation or mutations of FAM20C causes human Raine Syndrome, which manifests as lethal osteosclerosis bone dysplasia or non-lethal hypophosphatemia rickets. However, it is only hypophosphatemia rickets that was reported in the mice with Fam20c deletion or mutations. To further investigate the local and global impacts of Fam20c mutation, we constructed a knock-in allele carrying Fam20c mutation (D446N) found in the non-lethal Raine Syndrome. The Fam20c D446N allele replaced the WT Fam20c by 3.6Kb Col1a1-Cre to get the conditional knock-in mice, and by Hprt-cre to get conventional knock-in mice, respectively. Results The radiology, serum biochemistry and immunohistochemistry indicated that all conditional and most conventional Fam20c D446N knock-in mice displayed hypophosphatemic rickets with the increased Fgf23 and deceased Dmp1 expression, which survived to adulthood. However, a few conventional Fam20c D446N knock-in mice died before weaning with the osteosclerotic X-ray radiography, though micro-CT assay displayed a reduced mineral density and increased porosity in the osteosclerotic tibia. Our results suggested that hypophosphatemia rickets was the predominant phenotype in both conditional and conventional Fam20c deficient mice, while the lethal osteosclerotic phenotype occasionally took place in the conventional Fam20c mutant mice. Conclusion This finding also implicated that the osteosclerotic features resulting from Fam20c deficiency could be a semblance on the basis of rickets, which is most likely triggered by the alterations in the systems other than skeleton.